Reuse of rigid polyurethane foam waste in a thermoplastic polyurethane matrix (Research, Society and Development, 2020)
Polyurethanes are polymers prepared from the reaction between polyfunctional isocyanates and polyols, containing intramolecular urethane bonds. The thermosetting polyurethane (PUR) is a non-biodegradable polymer, that cannot be reprocessed by melting, so that the waste generated becomes an environmental problem. The objective of this study was to produce and characterize thermoplastic polyurethane (TPU) composites  incorporated with rigid polyurethane particles through  the  extrusion  process,  as  an  alternative  for  the  reuse  of  the  PUR  and improvement of the TPU properties.  Extruded composites with 10%, 20% and 30% in weight    were thermopressed and had their morphological, thermal and mechanical properties analyzed.  The composite with 20% of filler (TPU/PUR20%) presented the best results, with an increase of 117% in the elastic modulus and 79% in the yield stress when compared to the pure matrix (TPU/PUR0%). No additional increment of the mechanical properties was observed to the composite with 30% of PUR  (TPU/PUR30%), probably because of  the  greater  heterogeneity  of  this  composite,  related to  the  difficulty  of dispersion  and  distribution  of  the  high  content  of  the  PUR  particles  in  the  matrix. This study presented a viable alternative for the use and value aggregation of the thermoset polyurethane residue, contributing to minimize environmental impacts and to improve the properties of thermoplastic polyurethane.